2004
DOI: 10.1002/elsc.200402160
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Characterization and Application of Cyanide‐resistant Nitrile Hydratases

Abstract: Two new bacterial strains, Pseudomonas marginales MA32 and Pseudomonas putida MA113, containing nitrile hydratases resistant to cyanide were isolated from soil samples by an enrichment procedure. In contrast to known nitrile hydratases, which rapidly lose activity at low to moderate cyanide concentrations, the enzymes described in this paper tolerate up to 50 mM cyanide. They show a broad substrate spectrum including not only small substrates like acrylonitrile but also nitriles with longer side chains and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…lease cyanide because of decomposition, like a-hydroxy-or a-aminonitriles. [14] In HnL-catalysed hydrocyanation reactions, HCN is usually added in excess to drive the equilibrium to complete conversion. The stability of the NHase CLEA activity during incubation in the presence of different HCN concentrations is therefore of importance and was investigated (Figure 2 A).…”
Section: Stability Of Nhase Cleas Under Hnl Hydrocyanation Conditionsmentioning
confidence: 99%
“…lease cyanide because of decomposition, like a-hydroxy-or a-aminonitriles. [14] In HnL-catalysed hydrocyanation reactions, HCN is usually added in excess to drive the equilibrium to complete conversion. The stability of the NHase CLEA activity during incubation in the presence of different HCN concentrations is therefore of importance and was investigated (Figure 2 A).…”
Section: Stability Of Nhase Cleas Under Hnl Hydrocyanation Conditionsmentioning
confidence: 99%
“…Firstly, a bacterium, R. boritolerans CCTCC M 208108, which exhibited high NHase activity towards ADBN and cyanide resistance, was screened. Its cyanide-resistant capacity (5 mM) was much better than those of the other strains tested in this study ( Table 1) and that of R. erythropolis 870-AN019 (25 M) [5], but poorer than those of Pseudomonas marginales MA32, Pseudomonas putida MA113 (50 mM) [12], and Nitriliruptor alkaliphilus (11 mM) [30]. Moreover, product tolerance of an enzyme is also a parameter of great importance for high product accumulation.…”
Section: Discussionmentioning
confidence: 73%
“…In our findings, the substrate profile of R. qingshengii ZA0707 indicated that this strain harbored versatile NHase with a wide range of substrate spectrum. Moreover, strain ZA0707 was tolerant against cyanide up to 5 mM which was much higher value as compared to R. rhodochrous J1 (0.01 mM) (Nagasawa et al 1991) and R. erythropolis 870-AN019 (25 lM) (Brandão et al 2004) but lower than those of Pseudomonas marginales MA32, P. putida MA113 (50 mM) (Gerasimova et al 2004) and Nitriliruptor alkaliphilus (11 mM) (van Pelt et al 2009). Further work still needs to be carried out with ZA0707 to investigate this phenomenon.…”
Section: Discussionmentioning
confidence: 87%
“…For example, NHase of Rhodococcus erythropolis lost 50% of its activity with 25 lM KCN (Brandão et al 2004) while aaminonitriles and a-hydroxynitriles become unstable in aqueous solution and liberate cyanide (Brady et al 2004;Brandão et al 2004). Therefore, there is a need to explore new cyanide-resistant NHases for production of a-aminoamides and a-hydroxyamides (Gerasimova et al 2004).…”
Section: Introductionmentioning
confidence: 98%